A new synthetic cathinone: 3, 4‐EtPV or 3, 4‐Pr‐PipVP? An unsuccessful attempt to circumvent the German legislation on new psychoactive substances. Issue 1 (26th October 2022) - Pulver, Benedikt; Riedel, Jan; Westphal, Folker; Luhn, Steven; Schönberger, Torsten; Schäper, Jan; Auwärter, Volker; Luf, Anton; Pütz, Michael
Abstract: Synthetic cathinones comprise psychostimulants with desired effects like euphoria, increased vigilance, appetite suppression, and—mainly depending on certain structural features—entactogenic properties. 3, 4‐EtPV (1‐(bicyclo[4.2.0]octa‐1, 3, 5‐trien‐3‐yl)‐2‐(pyrrolidin‐1‐yl)pentan‐1‐one) was first mentioned in an online drug forum in September 2021, where its imminent synthesis was announced. The goal was to produce a legal alternative to the phenylethylamines already banned by the German NpSG. In February and June 2022, two samples labeled with the name and molecular structure of 3, 4‐EtPV were analyzed. The molecular structure of the obviously mislabeled compound was elucidated and comprehensively characterized within the ADEBAR project. The synthetic cathinone identified differed from the declared 3, 4‐EtPV by a 3, 4‐propylene bridge instead of a 3, 4‐ethylene bridge and a piperidine ring instead of a pyrrolidine ring. The short name 3, 4‐Pr‐PipVP (3, 4‐pr opylene‐2‐(1‐pip eridinyl)v alerop henone) was suggested as a semisystematic name in collaboration with the European Monitoring Centre for Drugs and Drug Addiction. Herein, the results of the analyses are discussed and will enable forensic laboratories to update their databases quickly and identify 3, 4‐Pr‐PipVP confidently. 3, 4‐Pr‐PipVP is already scheduled under the German NpSG. This study highlights that there are ongoing efforts to deliberately circumvent generic definitions given, for example, in the German NpSG and that (unintentional?) mislabeling can be an issue. The end user purchasing substances online can never be sure that the material actually supplied will be the one ordered, and he might receive an illicit drug instead of an uncontrolled one. Furthermore, the purity is always unknown, creating health risks due to unexpected effects and potencies. Abstract : The failed synthesis of 3, 4‐EtPV highlights the ongoing efforts to deliberately circumvent generic definitions, which is increasingly difficult to achieve. 3, 4‐Pr‐PipVP, identified in two samples (unintentionally?) mislabeled and advertised as "3, 4‐EtPV", is already scheduled under the German NpSG.